Pembuatan Aplikasi Mobile Sederhana sebagai Sarana Belajar untuk Siswa SMK Kota Cirebon - Nisa Dienwati Nuris; Raditya Danar Dana; Federicko Ramiro Firjatullah; Fifia Nur Handayani (CV. Multi Kreasi Media, 2022)
The rapid development of information and communication technology has had a significant impact in the world of education, including at the Vocational High School (SMK) level. The need for innovative and interactive learning media encourages the development of mobile applications as an effective learning tool. This research aims to design and build a simple mobile application that can be used by SMK students in Cirebon City as an additional learning media. The application was developed using the Android platform with the Java programming language and utilizing Android Studio as an Integrated Development Environment (IDE). The development method used is waterfall, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. The content in the application is adjusted to the SMK curriculum, especially in subjects that are practical. The test results show that the application runs well on various Android devices and gets a positive response from users in terms of ease of use and interface appearance. With this application, it is expected that the learning process will become more flexible, interactive, and support the achievement of student competencies optimally. In the future, the application can be further developed by adding features such as interactive practice questions, discussion forums, and integration with online databases to make it more dynamic.